Numerical simulation analysis of the stability of the construction face of a super long tunnel under conditions of precipitation and abundant water - Dun, Huoda; Chen, Song; Liu, Haitao; Chen, Chen; Zhang, Yuansheng; Yuan, Ying (Frontiers in Materials, 2024)
Tunnel construction in central and western China presents significant challenges primarily due to the complex geological conditions. The presence of water-rich zones compromises the stability of excavation faces, leading to potential safety risks and economic losses. This study investigates the Yingpan Mountain extra-long tunnel through numerical simulations, focusing on stress and displacement variations under varying conditions. The primary focus is on assessing the influence of water on tunnel stability, particularly under water-rich conditions. The study proposes effective evaluation methods for different construction stages. The findings offer valuable guidance for future engineering projects, thereby enhancing safety and efficiency in tunnel construction.